Phylogenomics and the falsification of shearwater species (Puffinus mauretanicus, P. yelkouan) hypotheses: a comment on - George Sangster; Meritxell Genovart; Tim Guilford; Daniel Oro; Maite Louzao; M. de L. Brooke; José Manuel Arcos (Molecular Phylogenetics and Evolution, 2026)

Map and compass navigation: the mechanism and ontogeny of animal maps - Joe Morford; Joe Wynn; Patrick Lewin; Paris Jaggers; Lewis Lancaster-Reeves; Adelaide Sibeaux; Oliver Padget; Tim Guilford (Animal Behaviour, 2025)

Almost there: Learning to navigate approximately with a grid map - Joe Morford; Patrick Lewin; Paris Jaggers; Joe Wynn; Tim Guilford; Oliver Padget (Behavioural Processes, 2025)

Pre-laying sex differences in reproductive roles can constrain foraging behaviour in a monomorphic seabird - Katrina Siddiqi-Davies; Lewis Lancaster-Reeves; Joe Morford; Oliver Padget; Joe Wynn; Sarah Bond; Patrick Lewin; Paris Jaggers; Tim Guilford (Marine Biology, 2025)
Sex differences in foraging behaviour can arise in monomorphic species when reproductive roles differ. How these differences shape foraging behaviour during the pre-laying period—an understudied reproductive stage in seabirds—remains unclear. In a monomorphic procellariform seabird, the Manx shearwater ( Puffinus puffinus ), we compare foraging behaviour between sexes during pre- and post-laying periods. Prior to laying, sex roles differ, with females synthesizing the egg, while males are thought to primarily engage in nest defence. We found that pre-laying females take longer at-sea trips that are more distant from the colony, whilst males visit the colony more frequently, and undertake more dives. For males, pre-laying dives are shallower than those during the post-laying period. Sex differences largely diminish post-laying, as reproductive roles become more equivalent between sexes. We suggest that increased colony visitation during pre-laying may constrain males to closer foraging sites and these may be of poorer quality than those reached by females. We found that colony visitation appears to restrict evening foraging opportunities for males, as birds must commute to the breeding site for nocturnal visits. Our results show that significant differences in reproductive roles before egg-laying can constrain at-sea foraging behaviour. Understanding these differences can facilitate understanding of how sex-specific foraging behaviour may interact with human-induced changes in marine environments.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Homing pigeon navigational ontogeny: no evidence that exposure to a novel release site is sufficient for learning - Joe Morford; Anna Gagliardo; Enrica Pollonara; Tim Guilford (Animal Behaviour, 2024)

Biochemical and molecular biomarkers and their association with anthropogenic chemicals in wintering Manx shearwaters (Puffinus puffinus) - Patricia P. Serafini; Bárbara P.H. Righetti; Ralph E.T. Vanstreels; Leandro Bugoni; Clei E. Piazza; Daína Lima; Jacó J. Mattos; Cristiane K.M. Kolesnikovas; Alice Pereira; Marcelo Maraschin; Isadora Piccinin; Tim Guilford; et al. (Marine Pollution Bulletin, 2024)

How might magnetic secular variation impact avian philopatry? - Joe Wynn; Oliver Padget; Joe Morford; Paris Jaggers; Katrina Davies; Emma Borsier; Tim Guilford (Journal of Comparative Physiology A, 2022)
A tendency to return to the natal/breeding site, ‘philopatry’, is widespread amongst migratory birds. It has been suggested that a magnetic ‘map’ could underpin such movements, though it is unclear how a magnetic map might be impacted by gradual drift in the Earth’s magnetic field (‘secular variation’). Here, using the International Geomagnetic Reference Field, we quantified how secular variation translates to movement in the implied positions at which combinations of different magnetic cues (inclination, declination and intensity) intersect, noting that the magnitude of such movements is determined by the magnitude of the movements of each of the two isolines, and the angle between their movement vectors. We propose that magnetic parameters varying in a near-parallel arrangement are unlikely to be used as a bi-coordinate map during philopatry, but that birds could use near-orthogonal magnetic gradient cues as a bi-coordinate map if augmented with navigation using more local cues. We further suggest that uni-coordinate magnetic information could also provide a philopatry mechanism that is substantially less impacted by secular variation than a bi-coordinate ‘map’. We propose that between-year shifts in the position of magnetic coordinates might provide a priori predictions for changes in the breeding sites of migratory birds.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Foraging flexibility and search patterns are unlinked during breeding in a free-ranging seabird - Akiko Shoji; Stéphane Aris-Brosou; Ellie Owen; Mark Bolton; Dave Boyle; Annette Fayet; Ben Dean; Holly Kirk; Robin Freeman; Chris Perrins; Tim Guilford (Marine Biology, 2016)

Flexible foraging strategies in a diving seabird with high flight cost - Akiko Shoji; Ellie Owen; Mark Bolton; Ben Dean; Holly Kirk; Annette Fayet; Dave Boyle; Robin Freeman; Chris Perrins; Stéphane Aris-Brosou; Tim Guilford (Marine Biology, 2014)

The Evolution of Multimodal Warning Displays - Candy Rowe; Tim Guilford (Evolutionary Ecology, 1999)